Carbon nanobowls supported ultrafine palladium nanocrystals: A highly active electrocatalyst for the formic acid oxidation. (23rd March 2017) - Jia, Nan; Shi, Yaru; Zhang, Shuxia; Chen, Xinbing; Chen, Pei; An, Zhongwei
Abstract: The carbon supporting materials play a crucial role for improving the utilization and electrocatalytic activity of noble metal nanocrystals. In this work, the high-quality carbon nanobowls (CNBs) with high surface area are synthesized successfully by a simple sol–gel synthetic method. Then, the as-prepared CNBs are used as advanced supporting material to anchor Pd nanocrystals by a facile homogeneous precipitation–reduction method. The as-prepared CNBs supported Pd nanocrystals (Pd/CNBs) nanohybrids are examined thoroughly by various physical characterizations. Physical measurements display that the CNBs facilitate the dispersion and anchorage of Pd nanocrystals due to their high surface area and abundant O-containing surface groups. Cyclic voltammetry, electrochemical impedance spectroscopy, and chronoamperometry measurements reveal that the Pd/CNBs nanohybrids have higher electrocatalytic activity and durability for the formic acid electro oxidation than Vulcan XC-72 carbon supported Pd nanocrystals (Pd/C-72) nanohybrids and commercial Pd/C electrocatalyst. Highlights: High-quality carbon nanobowls (CNBs) are synthesized. CNBs show higher surface area and graphitization degree than Vulcan XC-72 carbon. CNBs favor the dispersion and anchorage of Pd nanocrystals. Pd/CNBs show improved FAOR activity and durability compared with Pd/XC-72.